2017
DOI: 10.1007/s11046-017-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fungus Ball-Type Maxillary Sinusitis Due to Penicillium Roqueforti

Abstract: The Penicillium genera, encompassing about 225 different species of fungi, are naturally present in the environment. These genera are poorly linked to human disease, except for Penicillium marneffei causing septicemia in immunocompromised hosts. Thus, Penicillium species recovered from respiratory tract samples are often considered as inhaled contaminants in the clinical laboratory. However, we report here a case of fungal maxillary sinusitis due to Penicillium roqueforti diagnosed in a 40-year-old female, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The first report of human infection by this fungus was observed in 1973, when Penicillium marneffei isolation from the spleen of a patient with Hodgkin's disease was described (Disalvo et al, 1973). In fact, P. marneffei has been the most frequent species reported in human infections (Vanittanakom et al, 2006;Yu et al, 2018), although rare infections by other species have also been reported (Geltner et al, 2013;Oshikata et al, 2013;Radulesco et al, 2018).…”
Section: Genus Penicilliummentioning
confidence: 99%
“…The first report of human infection by this fungus was observed in 1973, when Penicillium marneffei isolation from the spleen of a patient with Hodgkin's disease was described (Disalvo et al, 1973). In fact, P. marneffei has been the most frequent species reported in human infections (Vanittanakom et al, 2006;Yu et al, 2018), although rare infections by other species have also been reported (Geltner et al, 2013;Oshikata et al, 2013;Radulesco et al, 2018).…”
Section: Genus Penicilliummentioning
confidence: 99%